2021
DOI: 10.7759/cureus.16152
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease-Associated Mucormycosis from a Tertiary Care Hospital in India: A Case Series

Abstract: Background: Coronavirus disease (COVID-19) remains a health concern with new challenges emerging as the pandemic progresses. The recent rise of opportunistic infections especially mucormycosis in COVID-19 patients is further complicating their outcomes. Mucormycosis is well known to infect patients with diabetes mellitus, malignancy, chemotherapy, and other immunocompromised conditions. The treatment of COVID-19 largely remains systemic steroids and other immunomodulators that add to the risk of invasive funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 29 publications
2
17
0
1
Order By: Relevance
“…Our findings indicated that a significant number of patients (72.2%) had received steroids for COVID-19. These findings were similar to previous studies, which reported that (84.6%) patients had received prior steroids for COVID-19[ 11 ]. Furthermore, our study revealed that 37% of the patient received oxygen therapy during hospitalization as a part of treatment for COVID-19 infection, which is very significant with the finding of another study where 57% of patient needed oxygen support for COVID-19 infection [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings indicated that a significant number of patients (72.2%) had received steroids for COVID-19. These findings were similar to previous studies, which reported that (84.6%) patients had received prior steroids for COVID-19[ 11 ]. Furthermore, our study revealed that 37% of the patient received oxygen therapy during hospitalization as a part of treatment for COVID-19 infection, which is very significant with the finding of another study where 57% of patient needed oxygen support for COVID-19 infection [ 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…[ 58 ] India Case series Single-center 5 [33–70] 20 (1) 100 (5) Singh Y. [ 59 ] India Case series Single-center 13 Nov 2020–Jan 2021 [5–75] 85 (11) 62 (8) Garg R. [ 60 ] India Case series Single-center 7 May 2021 [38–70] 71 (5) 100 (7) Arana C. [ 61 ] Spain Case series Single-center 2 [48–62] 100 (2) 50 (1) Barman Roy D. [ 62 ] India Case series Single-center 2 [39–50] 50 (1) 50 (1) Ashour MM. [ 63 ] Egypt Case series Single-center 6 [41–67] 50 (3) 100 (6) Pal P. [ 64 ] India Case series Single-center 10 ...…”
Section: Resultsmentioning
confidence: 99%
“…[ 58 ] 40 (2) 20 (1) 40 (2) Singh Y. [ 59 ] 46 (6) 15 (2) 23 (3) 85 (11) 69 (9) 77 (10) 77 (10) Garg R. [ 60 ] 29 (2) 0 (0) 100 (7) 0 (0) Arana C. [ 61 ] 100 (2) 100 (2) 100 (2) 100 (2) 0 (0) 100 (2) 50 (1) Barman Roy D. [ 62 ] 0 (0) 0(0) 50 (1) Ashour MM. [ 63 ] 17 (1) Pal P. [ 64 ] 10 (1) 30 (3) 80 (8) …”
Section: Resultsunclassified
“… Akinosoglou et al, 2021 , Banerjee et al, 2021 , Biswas, 2021 , CSSE, 2021 , CDC, 2021 , CDC, 2020 , Chaudhry et al, 1987 , Kontoyiannis et al, 2010 , Medicover Hospitals, 2021 , NIH, 2021 , Neblett Fanfair et al, 2012 , Ong et al, 2021 , Pappas et al, 2010 , Park et al, 2011 , Rees et al, 1998 , Singh et al, 2021a , Singh et al, 2021b .…”
Section: Uncited Referencesmentioning
confidence: 99%